Comparison between intravenous chemotherapy and intra-arterial chemotherapy for retinoblastoma: a meta-analysis - Qiuying Chen (BMC Cancer, 2018)
Abstract Background Intravenous chemotherapy (IVC) and intra-arterial chemotherapy (IAC) have become the primary treatments for retinoblastoma; however, some controversy remains over which method is more effective. We conducted a meta-analysis to compare the clinical efficacy of IVC and IAC. Methods We systematically searched literature published on PubMed, Embase, and Cochrane Library up to May 2017. Studies containing either IAC or IVC that reported on efficacy were included. The effects estimate was expressed as a pooled rate with 95% confidence interval (CI), using a fixed-effects or random-effects model. Results Twenty-six studies were identified which included 1541 eyes (IAC: 11 trials, 445 eyes; IVC: 16 trials, 1096 eyes). The mean follow-up times were 49.4 months (range, 13.0–105.3 months) for IVC and 21.7 months (range, 8.8–38.7 months) for IAC. For the International Classification of Intraocular Retinoblastoma (ICRB) grading, the overall success rate was higher with IAC than with IVC (75.7% [95%CI: 65.7%–83.6%] vs. 69.5% [95%CI: 51.9%–82.8%], P < 0.001). The globe salvage with IAC was higher than with IVC in group D eyes (79.5% [95%CI: 71.8%–85.4%] vs. 55.1% [95%CI: 45.6%–64.2%], P < 0.001), but not in groups B (95.8% [95%CI: 57.5%–99.7%] vs. 82.5% [95%CI: 58.9%–94.0%], P = 0.163), C (91.3% [95%CI: 65.9%–98.3%] vs. 89.0% [95%CI: 69.0%–96.7%], P = 0.212), and E eyes (51.2% [95%CI: 37.0%–65.2%] vs. 43.2% [95%CI: 18.3%–72.1%], P = 0.578). IAC and IVC were not significantly different regarding the recurrence and metastasis rates (15.0% vs. 15.4%, P = 0.148 and 2.7% vs. 0.6%, P = 0.194, respectively). For Reese-Ellsworth (RE) grading, IAC had a higher globe salvage in groups IV (90.9% [95%CI: 56.0%–98.7%] vs. 66.3% [95%CI: 32.4%–89.0%], P = 0.047) and V eyes (83.2% [95%CI: 72.0%–90.5%] vs. 59.9% [95%CI: 43.1%–74.6%], P = 0.003), but not in group I-III eyes (88.6% [95%CI: 58.3%–97.7%] vs. 88.1% [95%CI: 76.6%–94.4%], P = 0.244). The overall success rate was higher in IAC than in IVC (87.1% [95%CI: 78.1%–92.7%] vs. 77.3% [95%CI: 68.1%–84.4%], P = 0.033). Conclusions IAC may be superior to IVC for the treatment of retinoblastoma, with a higher overall success rate and higher globe salvage in group D or groups IV and V eyes.